CALIPH HARUN AL RASHID'S POLICY ON ARABIC LANGUAGE DEVELOPMENT DURING THE ABBASID PERIOD - Zulpina Zulpina; Muhammad Zaky Mawardie (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
This research aims to find out and examine the role of Caliph Harun Al Rashid in the development of Arabic during the Abbasid Dynasty. The questions to be answered through this research are (1) How was the role of Caliph Harun Al-Rashid in the government during the Abbasid Dynasty, and (3) How was the development of Arabic language during the period of Caliph Harun Al-Rashid? To answer these questions, the research used a literature approach. The research method used with the type of literary research, the primary data source is a book entitled Harun Al-Rashid Amir The Caliphs and the Greatest King in the World and the Glory of the Caliph Harun Ar-Rashid The Progress of World Civilization in the Golden Age of Islam. While the secondary data sources are other books that are relevant to the object of the author's discussion. The data processing method used is the content analysis method. The findings of the results of this study indicate that (1) Caliph Harun Al Rashid's policies in Arabic Language Development policies carried out by Caliph Harun ar-Rashid related to the development of Arabic in his time include making Arabic the official language of the State, the movement of translating manuscripts and Greek books, establishing Baitul Hikmah, Purification of Arabic, Kuttab and the establishment of literary institutions (2) The development of Arabic during the time of Caliph Harun Al Rashid was very rapid, which was marked by the development of literature, grammar, and the emergence of Arabic scholars